True "contradictions" and conflicts in the Talmud - Hulatt, Owen (Religious studies, 2025)
In this article, we consider the presence of what appear to be true contradictions in the Talmud. We consider and reject a glut-theoretic response. We argue these apparently contradictory Talmudic passages should be understood not as ordinary propositions, but as being given under an operator. This allows us to understand these rulings as genuinely conflicting, but not genuinely contradictory. We illustrate the broad shape of such a view through consideration of Hans Kelsen's late-period philosophy of law. We also consider and reject responses to this issue given by Rashi, R. Kook, and R. Feinstein. We close by considering why a system of Jewish law which allows for jointly affirmed conflicting propositions is desirable. We claim that if, as Maimonides suggests, the fundamental project of Jewish law is the eradication of idolatry, then the law itself should remind us that God's ways are higher than our ways. One way of doing so is to resist capture by a transparent set of principles, by allowing for conflicting rulings to be affirmed. This article does not presuppose familiarity with the Talmudic corpus or Jewish tradition.